A network meta-analysis of first-line treatment options for patients with Child-Pugh class B functional hepatocellular carcinoma: comparison of efficacy and safety - Zhang, Yu-Xuan; Wu, Jia-Yi; Wu, Jun-Yi; Zeng, Zhen-Xin; Pan, Rong-Jian; Ou, Xiang-Ye; Li, Yi-Nan; Yan, Mao-Lin (Frontiers in Pharmacology, 2026)
IntroductionManagement of patients with advanced hepatocellular carcinoma (HCC) and Child-Pugh class B liver function is challenging owing to compromised hepatic functional reserve, affecting treatment selection and outcomes, as many systemic therapies demonstrate altered pharmacokinetics and increased toxicity in this population. Current treatment guidelines predominantly focus on patients with preserved liver function (Child-Pugh A), creating a critical evidence gap for the optimal management of patients with Child-Pugh B liver function. This network meta-analysis (NMA) evaluated first-line therapies for patients with advanced HCC and Child-Pugh B cirrhosis, addressing current evidence gaps to guide optimal treatment selection for this high-risk population.MethodsThe PubMed, Embase, and Cochrane Library databases were searched until 31 October 2024. Randomized controlled trials and prospective cohort studies were included if they involved patients with advanced HCC and Child-Pugh class B liver function, evaluated first-line therapeutic agents, and reported overall survival (OS) and/or progression-free survival (PFS) with 95% confidence intervals. Bayesian NMA was employed to evaluate treatment efficacy and safety.ResultsEleven studies comprising 2,536 patients were included in the NMA. Lenvatinib exhibited the greatest probability of ideal efficacy for OS, while atezolizumab and bevacizumab combination therapy demonstrated the highest likelihood of optimal performance in terms of PFS. The overall incidence of adverse events (AEs) was 68.58%. The predominant grade 3–4 AEs included hypertension, proteinuria, hand-foot syndrome, and abnormal liver function.ConclusionAtezolizumab and bevacizumab combination therapy demonstrated the optimal net benefit regarding PFS and reduced toxicity, whereas lenvatinib monotherapy exhibited the greatest net benefit in OS but with increased toxicity.